Bio-inspiring Cyber Security and Cloud Services: Trends and Innovations - Hassanien, Aboul Ella; Kim, Tai-Hoon; Kacprzyk, Janusz; Awad, Ali Ismail (Intelligent Systems Reference Library, 2014)
This volume presents recent research in cyber security, and reports how organizations can gain competitive advantages by applying the different security techniques in real-world scenarios. The volume provides reviews of cutting-edge technologies, algorithms, applications and insights for bio-inspiring cyber security-based systems. The book will be a valuable companion and comprehensive reference for both postgraduate and senior undergraduate students who are taking a course in cyber security. The volume is organized in self-contained chapters to provide greatest reading flexibility.  .